Waterbirds as bioindicators of ecosystem health: seasonal dynamics in Tondano Lake, Indonesia - Djarang, Rievo; Harindah, Gerry; Suriani, Ni Wayan; Taulu, Marthy Lingkan Stella (Bioeksperimen: Jurnal Penelitian Biologi, 2026)
Waterbird diversity in Tondano Lake reflects ecological degradation caused by water-hyacinth invasion and sedimentation. This study analyzed the diversity and abundance of waterbirds in Tondano Lake, Indonesia, across wet (February-May) and dry (June-October) seasons in 2025 to assess their role as bioindicators of ecosystem health. Multi-season observations were carried out monthly along a 6.5 km transect at ten strategic points. Eight waterbird species from three families were recorded, with Egretta garzetta being the most abundant (29.1%) and Alcedo atthis the least (4.8%). The Shannon-Wiener diversity index (H' = 1.92) indicates a moderate level of species diversity, which reflects a pattern of ecological simplification when compared to pristine tropical lakes such as Lake Sentarum (H' = 2.5). Waterbird abundance showed significant negative correlations with water hyacinth density (r = -0.68, p = 0.032) and water depth (r = -0.72, p = 0.019), revealing that invasive vegetation and shoaling are primary drivers of habitat loss. These findings demonstrate that waterbirds function as sensitive bioindicators of ecological stress, highlighting the urgent need for integrated watershed management to prevent further community collapse.